Modeling the implementation of NDCs and the scenarios below 2°C for the Belt and Road countries. Issue 1 (16th December 2020) - Qimin, Chai; Sha, Fu; Xinyuan, Wen
ABSTRACT: In order to understand better on medium-and long-term climate change issues in international cooperation of the Belt and Road Initiative (BRI), this paper is meant to assess the implementation of National Determined Contributions (NDCs) of the BRI countries and the emission constraints under the Paris Agreement to hold the increase in the global average temperature to well below 2°C above pre-industrial levels, based on the Belt and Road Integrated Assessment Model (BRIAM) and the best available data. The results show that the BRI countries are expected to collectively reduce about 3.2 billion tons of CO2 emissions with the implementation of their NDCs by 2030. In order to achieve the global goal of 2°C, without appropriate mitigation burden sharing and enhanced climate finance support, the BRI countries will face big challenges to bridge the emission gaps. The investment in clean energy and related new infrastructures in BRI will rise sharply to above US100 trillion by the end of this century accordingly with the increase in carbon price, which will also eventually have a significant impact on the price of electricity and oversea freight transport in a connecting world.